Navigating stakeholder perspectives on hydrogen generation technologies: A Q-methodology study of current hydrogen production policy in South Korea - Lee, Youhyun; Kim, Young Jin; Lee, Min Chul (International Journal of Hydrogen Energy, 2025)
This study examines perceptions of hydrogen power generation technologies, particularly gray hydrogen, which is currently prevalent in South Korea. Given the international emphasis on reducing greenhouse gas emissions, hydrogen has emerged as a potential solution for achieving carbon neutrality; however, the perspectives on its environmental, economic, technological, and safety implications are varied. Using Q-methodology, we explored five expert typologies, each presenting a distinct perspective: environmental advocates favoring fuel cells, co-combustion technology proponents, safety-oriented skeptics, economic efficiency advocates, and policy-oriented supporters. Consequently, although environmental advocates emphasize the need for green hydrogen, economic and policy-oriented experts recognize the role of gray hydrogen as a transitional solution. Co-combustion power generation has a clear advantage in terms of cost effectiveness. From an environmental perspective, hydrogen fuel cell power generation is superior, and the greatest challenges for both technologies are safety and public acceptance. The findings highlight a complex landscape in which stakeholders must balance environmental goals, safety concerns, economic feasibility, and regulatory requirements. This study provides policy recommendations to guide the strategic direction of hydrogen technology in South Korea, suggesting that a gradual transition from gray to green hydrogen may be feasible with robust policy support and technological development.
Keywords: Cocombustion; Environmental advocates; Gray hydrogen policy; Hydrogen co-combustion; Hydrogen fuel cells; Hydrogen generation technology; Korean hydrogen policy; Policy-oriented; Q-methodology; South Korea; Gray hydrogen policy; Hydrogen co-combustion; Hydrogen fuel cell; Korean hydrogen policy; Q-methodology